Analysis of Hibah Cancellation in the Case Study of the Decision of the Religious Court of Palangka Raya City Number 301/PDT.G/2023/PA.PLK - Sari Raihana; Abdul Salam (Mir'ah: Family Law and Legal Culture, 2024)
This research discusses a grant dispute reflected in the Decision of the Palangka Raya Religious Court Number 301/Pdt.G/2023/PA.PLK, which relates to the annulment of a grant and the sale and purchase of land. In this case, the court canceled the Minutes of Grant Submission and the Land Sale and Purchase Agreement between the defendant and co-defendant, because they were considered invalid according to the law. This research aims to analyze the implementation of grant law in the context of Indonesian positive law and Islamic law, and investigate the effect of grant cancellation on inheritance rights. The research method used is normative law in examining the object under study, while the research approach is a conceptual approach as a descriptive-qualitative analysis to obtain conclusions that can be scientifically accounted for. The results show that the decision reflects the court's efforts to uphold the principles of justice and legal clarity in grant transactions and land sales and purchases, in accordance with applicable regulations. This annulment has an impact on the protection of legitimate inheritance rights, avoiding abuse or manipulation in the transfer of property rights.